POSKOLONIALISME1 DAN STUDI TEOLOGI Sebuah Pengantar - Robertus Wijanarko (Litbang STFT Widya Sasana Malang, 2008)
This article is an endeavor to exhibit the significance of Postcolonial Theory for the works of the contextual theology in Indonesia. The author suggests, postcolonial approach facilitates theologians to create their project to be an engaged and enganging theology. Postcolonial Theory, the author believes, offers the possibility to decolonize “Western” method of theology. Following Homi Bhabha’s terms, this approach is expected to enable Indonesian Theology “to break the continuity and the consensus of (hegemonic) common sense.” Taking R.S. Sugirtharajah’s biblical study as an example, the author shows that postcolonial approach offers critical attitudes and framework to identify and redefine any “colonizing” theological assumptions